Wacana Pariwisata Bali Dalam Pusaran Pandemi Covid-19 - I Dewa Gede Kusuma (Universitas Mahendradatta Denpasar, 2020)
Balinese people still depend on economy on tourism sector. This could become big problems because during Covid-19 pandemic, tourists are still not allowed to to visit other countries, especially Indonesia.This research used three theories, namely Michel Foucalt’s Power and Knowledge Theory, Jacques Derrida’s Deconstruction Theory, and Antonio Gramsci’s Hegemony Theory. The big swirl of the Covid-19 pandemic gave impacts to the tourism industry, agriculture, and other macro and micro sectors in Bali. Many tourism attractions experienced a decrease. This situa- tion became a tourism discourse that was very interesting to be studied.The Bali public which was very crowded with tourists has turned into a silent place. However, this pandemic would end although they are not sure when, but the people in Bali have their own way to survive. Many of them sell food and do other business.The effect of the Covid-19 pandemic closes many hotels and restaurants, work termination and finally, this leads to the people’s economy. This situation is explored deeper outside the shining tourism, that the needs of new jobs, food security, and education access are needed by the Balinese behind the pandemic problems.